Improvement of the quantitation method for the tdh+ Vibrio parahaemolyticus in molluscan shellfish based on most-probable- number, immunomagnetic separation, and loop-mediated isothermal amplification - Escalante-Maldonado, Oscar; Kayali, Ahmad Y.; Yamazaki, Wataru; Vuddhakul, Varaporn; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is a marine microorganism that can cause seafood-borne gastroenteritis in humans. The infection can be spread and has become a pandemic through the international trade of contaminated seafood. Strains carrying the tdh gene encoding the thermostable direct hemolysin (TDH) and/or the trh gene encoding the TDH-related hemolysin (TRH) are considered to be pathogenic with the former gene being the most frequently found in clinical strains. However, their distribution frequency in environmental isolates is below 1%. Thus, very sensitive methods are required for detection and quantitation of tdh+ strains in seafood. We previously reported a method to detect and quantify tdh+ V. parahaemolyticus in seafood. This method consists of three components: the most-probable-number (MPN), the immunomagnetic separation (IMS) targeting all established K antigens, and the loop-mediated isothermal amplification (LAMP) targeting the tdh gene. However, this method faces regional issues in tropical zones of the world. Technicians have difficulties in securing dependable reagents in high-temperature climates where we found MPN underestimation in samples having tdh+ strains as well as other microorganisms present at high concentrations. In the present study, we solved the underestimation problem associated with the salt polymyxin broth enrichment for the MPN component and with the immunomagnetic bead-target association for the IMS component. We also improved the supply and maintenance of the dependable reagents by introducing a dried reagent system to the LAMP component. The modified method is specific, sensitive, quick and easy and applicable regardless of the concentrations of tdh+ V. parahaemolyticus. Therefore, we conclude this modified method is useful in world tropical, sub-tropical and temperate zones.